Forensic timber identification: a case study of a CITES listed species, Gonystylus bancanus (Thymelaeaceae). (July 2016) - Ng, Kevin Kit Siong; Lee, Soon Leong; Tnah, Lee Hong; Nurul-Farhanah, Zakaria; Ng, Chin Hong; Lee, Chai Ting; Tani, Naoki; Diway, Bibian; Lai, Pei Sing; Khoo, Eyen
Highlights: Genetic identification databases developed for a CITES listed species, G. bancanus . DNA barcode sequence variation allowed 90% of Gonystylus species to be resolved. 6 cpDNA regions with informative variable sites can distinguish G. bancanus populations from West and East Malaysia. 16 STRs were used to develop the DNA profiling databases for individual identification. Genetic identification databases developed can support forensic applications and help safeguard the species. Abstract: Illegal logging and smuggling of Gonystylus bancanus (Thymelaeaceae) poses a serious threat to this fragile valuable peat swamp timber species. Using G. bancanus as a case study, DNA markers were used to develop identification databases at the species, population and individual level. The species level database for Gonystylus comprised of an rDNA (ITS2) and two cpDNA ( trnH-psbA and trnL ) markers based on a 20 Gonystylus species database. When concatenated, taxonomic species recognition was achieved with a resolution of 90% (18 out of the 20 species). In addition, based on 17 natural populations of G. bancanus throughout West (Peninsular Malaysia) and East (Sabah and Sarawak) Malaysia, population and individual identification databases were developed using cpDNA and STR markers respectively. A haplotype distribution map for Malaysia was generated using six cpDNA markers, resulting in 12 unique multilocus haplotypes, from 24 informative intraspecific variable sites. These unique haplotypes suggest a clear genetic structuring of West and East regions. A simulation procedure based on the composition of the samples was used to test whether a suspected sample conformed to a given regional origin. Overall, the observed type I and II errors of the databases showed good concordance with the predicted 5% threshold which indicates that the databases were useful in revealing provenance and establishing conformity of samples from West and East Malaysia. Sixteen STRs were used to develop the DNA profiling databases for individual identification. Bayesian clustering analyses divided the 17 populations into two main genetic clusters, corresponding to the regions of West and East Malaysia. Population substructuring ( K = 2) was observed within each region. After removal of bias resulting from sampling effects and population subdivision, conservativeness tests showed that the West and East Malaysia databases were conservative. This suggests that both databases can be used independently for random match probability estimation within respective regions. The reliability of the databases was further determined by independent self-assignment tests based on the likelihood of each individual's multilocus genotype occurring in each identified population, genetic cluster and region with an average percentage of correctly assigned individuals of 54.80%, 99.60% and 100% respectively. Thus, after appropriate validation, the genetic identification databases developed for G. bancanus in this study could support forensic applications and help safeguard this valuable species into the future.